Cases of Civil Matter: Riley County, Kansas District Court Cases and Its Role on Poverty, Crime and Family from 1934-1935 - Jackman, Alexandra (Kansas State University. Dept. of History, 2013)
The trial of one Ronald Finney captivated the residents of Manhattan, Kansas and it was a fascination attributed due to the dire economic circumstances that these Kansans faced in 1934-1935. Finney’s white collar crime was, however, unreflective of the lawsuits typically conducted within Riley County at that time. Civil cases dealing mostly with the forefeiture of lands made up the most of the cases prosecuted in Riley County at the time, dwarfing criminal cases by a large margin. Through looking at the court dockets between 1934 and 1935, one can see the ways in which the Dust Bowl affected the residents of Manhattan and Riley County in the realms of the economy and the family. The Dust Bowl affected Riley County much like the rest of the Midwest, with unyielding crops and an eroded topsoil. The economic hit to the county can be seen by the large amount of civil cases arising from indebtedness, forfeitures, and sheriff sales. Riley County benefited greatly from the federal and state relief programs, which helped to curb crime rates in response to reduced economic activity and opportunity, except in Manhattan which was additionally aided by the existence of the Kansas State Agricultural College and the economic participation it engendered. While federal programs kept society intact in regards to crime, individual hardship can be seen in the relatively high numbers of divorce as well as rural land sales.
Keywords: Riley County; Great Depression; Manhattan, Kansas; New Deal; Court cases